A 2.5-D frequency-domain nonlinear computer model of coupled-cavity traveling wave tubes. Issue 5 (26th August 2014) - Bai, Chun-Jiang; Li, Jian-Qing; Hu, Yu-Lu
Abstract : Purpose: – The purpose of this paper is to present a 2.5-dimensional (2.5-D) frequency-domain nonlinear computer model for the beam-wave interaction of coupled-cavity traveling wave tubes (CC-TWTs). Design/methodology/approach: – MKK (proposed by Malykhin, Konnov, and Komarov) equivalent circuit model is used to describe the coupled-cavity slow-wave structure. And the losses are taken into account in the MKK equivalent circuit. Instead of one-dimensional (1-D) disk model, the electron beam is divided into a set of discrete rays and the electron dynamics are treated using the three-dimensional (3-D) Lorentz force equations. Findings: – The simulated result obtained show that the computer model can give a good predict for CC-TWTs in V-band. Practical implications: – The computer model is capable of treating nonlinear problems. Compared with particle-in-cell simulation, the 2.5-D frequency-domain computer model spends less time. Besides, the 3-D electron trajectory can be used to design high-efficiency collectors for CC-TWTs. Originality/value: – The computer model is able to simulate nonlinear problems of coupled-cavity TWT faster.